The impact of data entry structures on perceptions of individuals with chronic mental disorders and physical diseases towards health information sharing. (September 2020) - Esmaeilzadeh, Pouyan; Mirzaei, Tala; Dharanikota, Spurthy
Highlights: Little is known about whether individuals with different diseases (mental and physical) care for the data entry structure in sharing health information. We conduct four experiments to examine the impact of different types of health problems and the degree of data entry interfaces on patients' perception of information quality. Individuals with physical illnesses favor structured interfaces for their format, which are brief, comprehensive, accessible, useful, and understandable. Individuals with mental disorders prefer structured data interfaces due to lower perceived privacy, stigma, and psychological risk. The best level of data entry structure should be used consistent with patients' type of diseases to improve the success of health information exchange (HIE) networks. Abstract: Background and objective: Collecting, integrating, and sharing mental and physical health information can enhance the care process of patients and improve the completeness of patient databases in the health information exchange (HIE) networks. There is a need to encourage patients with physical and mental disorders to share their health information with providers. Data entry interfaces are suggested as an important factor affecting the quality of information. However, little is known about whether individuals with different diseases (mental and physical) care for the data entry structure in sharing personal health information (PHI). Materials and methods: We conduct four experiments to examine the impact of different health problems (mental vs. physical) and types of data entry interfaces (structured vs. unstructured) on individuals' perceptions of information quality and their willingness to share their health information. Results: Findings demonstrate that the type of disease and degree of data entry structure significantly influence individuals' perceptions of usefulness, accessibility, concise presentation, understandability, psychological risk, privacy concern, stigma, and willingness to share health information. Discussion: People with mental disorders prefer structured data interfaces as they perceive that a high degree of data entry structure can protect their privacy and mitigate stigma and psychological risk more than unstructured interfaces. Individuals with physical illnesses favor structured interfaces for their format, which is brief, comprehensive, accessible, useful, and understandable. People suffering from physical diseases are more likely to share their information when a highly-structured data entry interface is used. Moreover, individuals with mental disorders are less likely to disclose their information when providers collect health records using an unstructured data entry interface. Conclusions: This study suggests that the best level of structure for data entry interfaces could be designed at the point of care consistent with patients' health status and their type of diseases to improve the success of HIE networks.